SOSIALISASI DAN PENGENALAN KARTU WARNA TINJA: STRATEGI PENINGKATAN PENGETAHUAN TENAGA KESEHATAN DALAM SKRINING ATRESIA BILIER - Martono Tri Utomo; Rendi Aji Prihaningtyas; Yovani Savitri; Bagus Setyoboedi; Sjamsul Arief (Jurnal Abdi Insani, 2025)
Jaundice in newborns is a common condition, but it is important to distinguish between physiological and pathological forms. One of the main causes of pathological jaundice is cholestasis, with biliary atresia being the most frequent etiology. Biliary atresia is progressive and potentially fatal if treatment is delayed. Early detection is a key to successful therapy; however, limited knowledge among healthcare workers and inadequate screening tools contribute to delayed referrals. This study aimed to improve healthcare workers’ understanding of early detection of biliary atresia through education and introduction of stool color cards at RSUD dr. Sayidiman, Magetan. This study employed a quasi-experimental pre-test–post-test design involving 83 healthcare workers. Educational sessions were delivered by a pediatric gastrohepatology specialist, and participants completed questionnaires before (pre-test) and after (post-test) the intervention. Data were analyzed using the Wilcoxon signed-rank test to assess the improvement in knowledge scores, with statistical significance set at p < 0.05. A total of 83 participants took part, predominantly female (94%) with the largest age group being 30–39 years (43.4%). Most participants had more than 5 years of work experience (79.5%) and held a bachelor’s degree (55.4%). The mean knowledge score increased significantly from 90 in the pre-test to 95.3 in the post-test (p < 0.001). Socialization and introduction of stool color cards effectively improve healthcare workers’ knowledge regarding early detection of biliary atresia.